MANAJEMEN RADIO UNTUK MENGELOLA PENDENGAR ANAK MUDA (Studi Deskriptif Kualitatif Mengenai Manajemen Penyiaran di Solo Radio) - Veronita, Monica; Ruthnia, Firdastin; Wiryawan, Hari (KOMUNITAS, 2013)
The objective of the research is to determine the radio management that applied for manageÂ  theÂ  youngÂ  listenerÂ  segmentationÂ  inÂ  soloradio.Â  ThisÂ  researchÂ  belongÂ  toÂ  qualitative descriptiveÂ  studyÂ  thatÂ  emphasizeÂ  howÂ  toÂ  understandingÂ  theÂ Â  phenomenonÂ  ofÂ  theÂ  experience with describe it into speech. TheÂ  resultsÂ  ofÂ  thisÂ  researchÂ  isÂ  broadcastingÂ  managementÂ  ofÂ  soloradioÂ  ofÂ  soloradio usingÂ  4Â  stagesÂ  itÂ  isÂ  ,Â  planning,Â  organizing,Â  actuatingÂ  andÂ  controlling.Â  InÂ  theÂ  management, planning is good enough with the weekly meeting, monthly and yearly for planning programs thatâs compatible for young segmentation. Organizing is neatly supported by adequate human resources and the selection of the target youth broadcaster to be broadcast by both the sound according to the type of young people . Actuating done by providing guidance , motivation andÂ  good relationsÂ  with theÂ  presentÂ  approach to doingÂ  good broadcasting programÂ  andÂ  in accordanceÂ  withÂ  theÂ  youngÂ  listenersÂ  byÂ  joiningÂ  inÂ  everyÂ  eventÂ  organizedÂ  .Â  AsÂ  forÂ  the controlling is done by a general manager who is directly and indirectly. But for the head of theÂ  divisionÂ  asÂ  programÂ  directorÂ  toÂ  superviseÂ  directlyÂ  dueÂ  overseesÂ  announcerÂ  duringÂ  the broadcast to keep it out of the path of a young.